GLOBAL INTEREST RATE DYNAMICS AND THEIR IMPLICATIONS FOR THE COST OF CAPITAL: A SYSTEMATIC LITERATURE REVIEW COMPARING DEVELOPED AND DEVELOPING COUNTRIES - Muhammad Iqbal Harahap; Ahmad Kodri Fauzi Hasibuan; Khaira Amalia Fachrudin (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to analyze the dynamics of global interest rates and their impact on the cost of capital. Using the Systematic Literature Review (SLR) method, this study identifies, evaluates, and synthesizes scientific literature published between 2020 and 2025, and integrates macroeconomic data from the Trading Economics database. The analysis shows that the global Weighted Average Cost of Capital (WACC) has experienced a significant increase, from an average of 7.00% in 2020 to 8.00% in 2024, driven by increases in the risk-free interest rate and market risk premium. The findings of this study reveal asymmetric heterogeneity in impacts: interest rates in developed countries are more influenced by global and regional factors (above 50%), while in developing countries, domestic factors still dominate (77.9%), although vulnerability to fiscal spillovers from the United States remains high. In addition, high interest rates are found to hinder investment in strategic sectors, particularly capital-intensive renewable energy projects. This study concludes that companies need to adopt artificial intelligence (AI)-based financial management systems for real-time monitoring of capital costs and strengthening ESG performance to mitigate funding risks amid global market volatility.